ISOLATION AND PURIFICATION OF A KRINGLE 5 FROM HUMAN PLASMINOGEN USING AH-SEPHAROSE - Kapustianenko L. G.; Iatsenko T. A.; Iusova O. I.; Grinenko T. V. (Biotechnologia Acta, 2014)
Our aim was to develop a method for isolation of human plasminogen kringle 5 possessing functional activity. The proposed method includes the following steps: hydrolysis of plasminogen with elastase, separation of mini-plasminogen from kringle fragments 1–3 and 4 on Lys-Sepharose, mini-plasminogen hydrolysis with pepsin, affinity chromatography on AH-Sepharose and polyacrilamide gel electrophoresis.